Taxonomies of technological knowledge in higher education: A mapping of students’ perceptions - Staddon, Rachel (Australasian Journal of Educational Technology, 2022)
This paper presents the findings from a qualitative study exploring students’ perceptions of what constitutes technological knowledge. Technological knowledge dimensions from previous literature do not seem to be student-led, but rather suggested by the authors. It is therefore important to incorporate student views in order to create a more evidence-based taxonomy. Previous taxonomies of technological knowledge are also heavily linked to engineering-related disciplines, however definitions for use across the field of education and learning technologies would be helpful. In this study, a sample of student volunteers were interviewed about their understanding of technology enhanced learning and technological knowledge. The students were from a range of disciplines, not just engineering and science, so that technology knowledge for the general student population would be represented. An inductive thematic analysis was then carried out on the interview transcripts. Three knowledge types were derived from the thematic analysis: practical knowledge; structural knowledge; and computer science knowledge. These three empirically-derived technological dimensions were then mapped onto existing taxonomical structures from the literature. Finally, this paper discusses the implications of the student-generated dimensions for educators. Implications for practice or policy: Educators may need to consider how student-generated types of technological knowledge map onto existing technological knowledge structures and Bloom’s taxonomy. Educators can use the types of technology knowledge to target their teaching to their learners’ required knowledge level.